Cytochrome P450 2C9-mediated interactions: molecular docking studies of natural anti-arthritic compounds - Boon Hooi Tan; Nafees Ahemad; Yan Pan; Uma Devi Palanisamy; Chin Eng Ong (Exploration of Drug Science)
Aim: This study aimed to elucidate the structural basis for the interaction of five natural anti-arthritic compounds, diacerein, rhein, glucosamines [glucosamine 3-sulfate (G3S), and glucosamine 6-sulfate (G6S)], and chondroitin disaccharide Δdi-4S (C4S) with cytochrome P450 2C9 (CYP2C9). Methods: The investigated compounds were docked individually to the defined binding site in CYP2C9 based on the published crystal structure (PDB code: 1R9O). Results: All investigated ligands bound deep in the active site pocket in close proximity to the heme. Except for chondroitin, all ligands are bonded to residues found in critical secondary structures that form the boundary of the active site cavity, including B-C loop, F helix, F-G loop, and I helix. A total of 12 amino acids were involved in the binding, and all were critical residues located in four out of six substrate recognition sites (SRSs) that have been identified as important substrate binding and catalysis regions in other CYP isoforms. The relatively more potent binding (lower CDOCKER interaction energy) observed for diacerein and rhein compared to glucosamines and C4S are likely due to two main factors: a higher number of bonds between the ligand molecule and CYP2C9 active site residues (14 versus 0–4), and direct interaction with the heme moiety. The binding residues identified in both diacerein and rhein were the residues that also bonded with sulfaphenazole, the specific and potent CYP2C9 inhibitor. Conclusions: Collectively, this study has provided insights into structural features of CYP2C9 critical for inhibition and formed a basis for further exploration of structural determinants for potency and specificity of therapeutic compounds as CYP2C9 inhibitors.